Comparative Genomics - Xia, Xuhua (SpringerBriefs in Genetics, 2013)
This book provides an evolutionary conceptual framework for comparative genomics, with the ultimate objective of understanding the loss and gain of genes during evolution, the interactions among gene products, and the relationship between genotype, phenotype and the environment. The many examples in the book have been carefully chosen from primary research literature based on two criteria: their biological insight and their pedagogical merit. The phylogeny-based comparative methods, involving both continuous and discrete variables, often represent a stumbling block for many students entering the field of comparative genomics. They are numerically illustrated and explained in great detail. The book is intended for researchers new to the field, i.e., advanced undergraduate students, postgraduates and postdoctoral fellows, although professional researchers who are not in the area of comparative genomics will also find the book informative.